The influence of job characteristics,communication satisfaction and conscientiousness on organizational citizenship behavior (OCB) of sungai penuh city sme cooperative office employees - Jaya, Askar; Paspitawati, Paspitawati; Desfitriyana, Desfitriyana; Dewi, Rita Kumala; Mizarwan, Mizarwan (Institute of Computer Science (IOCS), 2024)
This study aims to look at the influence of Job characteristics on OCB employees of the SME Cooperative Service of Sungai Penuh City.) Communication Satisfaction on OCB of employees of the SME Cooperative Service of Sungai Penuh City. Conscientiousness on OCB of employees of the SME Cooperative Service of Sungai Penuh City. Job Characteristics, Communication Satisfaction and Conscientiousness together on OCB of employees of the SME Cooperative Service of Sungai Penuh City. This study uses a type of quantitative research method, where the sampling technique uses total sampling technique, with a sample size of 49 employees of the SME Cooperative Service of Sungai Penuh City. The analysis technique is multiple regression analysis. The results of this study indicate that Job characteristics have a positive influence on OCB employees of the SME Cooperative Service of Sungai Penuh City. Communication satisfaction has a positive influence on OCB employees of the SME Cooperative Service of Sungai Penuh City. Conscientiousness has a positive influence on OCB of employees of the SME Cooperative Service of Sungai Penuh City. Job characteristics, communication satisfaction and conscientiousness together have a significant effect on OCB of employees of the SME Cooperative Service of Sungai Penuh City.